Analysis of The Effectiveness of The Slum Management Program By The PRKP Agency - Sumawijaya, Hendri; Tjenreng , Muhammad Baharuddin Zubakhrum (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the effectiveness of the slum area management program implemented by the Housing, Settlement, and Land Agency (PRKP) of South Tangerang City. The research evaluates how the program contributes to improving residential environmental quality and community welfare, focusing on planning, implementation, community participation, and post-program sustainability. Methodology/approach: A qualitative descriptive approach was employed, combining field observations in selected sub-districts, in-depth interviews with PRKP officials and local residents, and document analysis. The study assessed program effectiveness using four key indicators: planning, execution, community involvement, and post-program impact. Results/findings: The findings indicate that while the program has achieved significant physical improvements in slum areas, gaps remain in social empowerment, long-term sustainability, and active citizen engagement. Key outcomes include enhanced infrastructure and living conditions, though challenges such as weak multi-stakeholder collaboration and limited community ownership persist. Conclusions: The PRKP program improved infrastructure but lacked sustainability. Greater community involvement and stronger local governance are crucial for lasting results. Limitations: This study is geographically limited to South Tangerang City and may not fully represent slum management challenges in other regions. The short-term assessment period also restricted the evaluation of long-term program sustainability. Contribution: The research provides actionable recommendations for strengthening slum area governance, including fostering multi-sector collaboration, increasing local community participation, and integrating economic empowerment initiatives. The findings offer insights for policymakers and urban planners in designing sustainable and inclusive slum-upgrading programs.